Feasibility of Fitness Tracker Usage to Assess Activity Level and Toxicities in Patients With Colorectal Cancer. (2021) - Ward, William H.; Meeker, Caitlin R.; Handorf, Elizabeth; Hill, Maureen V.; Einarson, Margret; Alpaugh, R. Katherine; Holden, Thomas L.; Astsaturov, Igor; Denlinger, Crystal S.; Hall, Michael J.; Reddy, Sanjay S.; Sigurdson, Elin R.; et al.
Abstract : PURPOSE: Performance status (PS) is a subjective assessment of patients' overall health. Quantification of physical activity using a wearable tracker (Fitbit Charge [FC]) may provide an objective measure of patient's overall PS and treatment tolerance. MATERIALS AND METHODS: Patients with colorectal cancer were prospectively enrolled into two cohorts (medical and surgical) and asked to wear FC for 4 days at baseline (start of new chemotherapy [± 4 weeks] or prior to curative resection) and follow-up (4 weeks [± 2 weeks] after initial assessment in medical and postoperative discharge in surgical cohort). Primary end point was feasibility, defined as 75% of patients wearing FC for at least 12 hours/d, 3 of 4 assigned days. Mean steps per day (SPD) were correlated with toxicities of interest (postoperative complication or ≥ grade 3 toxicity). A cutoff of 5, 000 SPD was selected to compare outcomes. RESULTS: Eighty patients were accrued over 3 years with 55% males and a median age of 59.5 years. Feasibility end point was met with 68 patients (85%) wearing FC more than predefined duration and majority (91%) finding its use acceptable. The mean SPD count for patients with PS 0 was 6, 313, and for those with PS 1, it was 2, 925 (122 and 54 active minutes, respectively) ( P = .0003). Occurrence of toxicity of interest was lower among patients with SPD > 5, 000 (7 of 33, 21%) compared with those with SPD < 5, 000 (14 of 43, 32%), although not significant ( P = .31). CONCLUSION: Assessment of physical activity with FC is feasible in patients with colorectal cancer and well-accepted. SPD may serve as an adjunct to PS assessment and a possible tool to help predict toxicities, regardless of type of therapy. Future studies incorporating FC can standardize patient assessment and help identify vulnerable population.